2018
DOI: 10.1016/j.nuclphysb.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Texture zero neutrino models and their connection with resonant leptogenesis

Abstract: Within the low scale resonant leptogenesis scenario, the cosmological CP asymmetry may arise by radiative corrections through the charged lepton Yukawa couplings. While in some cases, as one expects, decisive role is played by the λ τ coupling, we show that in specific neutrino textures only by inclusion of the λ µ the cosmological CP violation is generated at 1-loop level.With the purpose to relate the cosmological CP violation to the leptonic CP phase δ, we consider an extension of MSSM with two right handed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…We proceed to discuss an appealing scenario that the extremely small mass splitting between M 1 and M 2 needed for realizing the low-scale resonant leptogenesis scenario is due to the RGE running effects [170,171,172,173,174,175]. At a superhigh scale Λ (such as the GUT scale) where the heavy Majorana neutrino masses are generated, N 1 and N 2 are assumed to possess the exactly degenerate masses; namely, M 1 = M 2 ≡ M 0 < Λ.…”
Section: Rge Effects On Leptogenesismentioning
confidence: 99%
“…We proceed to discuss an appealing scenario that the extremely small mass splitting between M 1 and M 2 needed for realizing the low-scale resonant leptogenesis scenario is due to the RGE running effects [170,171,172,173,174,175]. At a superhigh scale Λ (such as the GUT scale) where the heavy Majorana neutrino masses are generated, N 1 and N 2 are assumed to possess the exactly degenerate masses; namely, M 1 = M 2 ≡ M 0 < Λ.…”
Section: Rge Effects On Leptogenesismentioning
confidence: 99%
“…We proceed to discuss an appealing scenario that the extremely small mass splitting between M 1 and M 2 needed for realizing the low-scale resonant leptogenesis scenario is due to the RGE running effects [172][173][174][175][176][177]. At a superhigh scale Λ (such as the GUT scale) where the heavy Majorana neutrino masses are generated, N 1 and N 2 are assumed to possess the exactly degenerate masses; namely, M 1 = M 2 ≡ M 0 < Λ.…”
Section: Rge Effects On Leptogenesismentioning
confidence: 99%
“…Several approaches have been proposed to explain neutrino data [11], being the two RH neutrino extension of the SM (2RHνSM) [12,13] a framework often considered [14][15][16][17][18][19][20][21], also in the context of leptogenesis [22][23][24][25][26][27][28][29][30][31][32][33]. Following the Occam's razor spirit, previous studies have shown that the 2RHνSM with texture-zero Yukawa and mass matrices is not compatible with data for a NO spectrum [3,[34][35][36][37][38][39].…”
mentioning
confidence: 99%